Gummy Smile Correction Using Lingual Orthodontics and Augmented Corticotomy in Extremely Thin Alveolar Housing. Issue 7 (October 2017) - Nahm, Kyung-Yen; Shin, Seung-Yun; Ahn, Hyo-Won; Kim, Seong-Hun; Nelson, Gerald
Abstract : Background: Tooth movement out of anatomic limitations was assisted by augmented corticotomy using deproteinized bovine bone mineral. Methods: Lip protrusion can be reduced by premolar extraction followed by retraction of the anterior teeth. Surgical intervention is appropriate when the alveolar bone housing of the anterior region is insufficient for the tooth movement. In this patient, corticotomy in upper palatal area and anterior segmented osteotomy in the mandible were performed. Anatomic limitation to the retraction was expanded by xenograft. An antero-posterior lingual appliance was used to bodily retract the upper anterior teeth. The gummy smile was resolved by intrusion of upper entire arch using 2 mid-palatal temporary skeletal anchorage devices. Results: New bone formation was observed on palatal side of upper anterior teeth. The teeth were moved into augmented area without fenestration or vitality loss. Lip protrusion was resolved, and the gummy smile was effectively improved. Conclusions: Orthodontic tooth movement beyond the limitation of the alveolar bone housing can be achieved with surgical assistance, which can be performed under local anesthesia. Without orthognathic surgery, the gummy smile can be reduced using an antero-posterior lingual retractor with mid-palatal skeletal anchorage.